2017
DOI: 10.1111/ijfs.13569
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted degradation of chitosan with hydrogen peroxide treatment using Box‐Behnken design for enhanced antibacterial activity

Abstract: SummaryLow molecular mass (MM) chitosan with high degree of deacetylation (DDA) has excellent bioactivity including antioxidant, antibacterial and encapsulation properties. In this work, to reduce the MM of chitosan, microwave-assisted heating treatment (MAHT) conditions were investigated using three factors at three levels Box-Behnken design (BBD). Microwave heating (MH) time, H 2 O 2 concentration and solid-toliquid ratio significantly affected the DDA and MM of chitosan. The antibacterial activities of chit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 47 publications
(61 reference statements)
1
5
1
Order By: Relevance
“…The average M w of OCS reduced significantly from 7 kDa to 2 kDa as H 2 O 2 concentration increased from 5% to 15%. The trend is similar to previous studies employing microwave-assisted H 2 O 2 treatment under different experimental conditions (i.e., H 2 O 2 concentration, microwave reaction time, microwave power, and so on) [ 20 , 23 , 37 ]. In this study, we used a relatively high concentration of H 2 O 2 that significantly reduced the reaction time to only 3 min as compared to the previous study that used a low concentration of H 2 O 2 and required a longer reaction time (more than 10 min) to obtain OCS of less than 2 kDa [ 20 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The average M w of OCS reduced significantly from 7 kDa to 2 kDa as H 2 O 2 concentration increased from 5% to 15%. The trend is similar to previous studies employing microwave-assisted H 2 O 2 treatment under different experimental conditions (i.e., H 2 O 2 concentration, microwave reaction time, microwave power, and so on) [ 20 , 23 , 37 ]. In this study, we used a relatively high concentration of H 2 O 2 that significantly reduced the reaction time to only 3 min as compared to the previous study that used a low concentration of H 2 O 2 and required a longer reaction time (more than 10 min) to obtain OCS of less than 2 kDa [ 20 ].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we used a relatively high concentration of H 2 O 2 that significantly reduced the reaction time to only 3 min as compared to the previous study that used a low concentration of H 2 O 2 and required a longer reaction time (more than 10 min) to obtain OCS of less than 2 kDa [ 20 ]. Further, the DD and the M w of OCS5% obtained in this study was much higher and lower, respectively, compared to these values reported in Zhang et al that used shorter microwave time (75 s) although higher microwave power (650 W) and lower H 2 O 2 concentration (2%) [ 37 ].…”
Section: Discussioncontrasting
confidence: 61%
“…Chitosan, a deacetylated derivative of chitin, is a natural biopolymer (No et al ., ; Feng et al ., ) that has been extensively studied for their antimicrobial and antifungal activities (No et al ., ; Kong et al ., ; Khan et al ., ; Zhang et al ., ). The antimicrobial activity of chitosan can be affected by intrinsic factors (molecular weight, (MW), degree of deacetylation (DD), solubility, etc.…”
Section: Introductionmentioning
confidence: 97%
“…Chitosan is a biopolymer produced from chitin, an abundant natural polymer present in the exoskeleton of shrimp, crabs, and other crustaceans [ 15 ]. Chitosan is a remarkable polymer with an impressive scope of versatile and diverse applications: as of 2022, chitosan covers up to 1 million citations on Google Scholar, with its biodegradability, biological compatibility, antimicrobial and antioxidant, and non-toxic nature paving its numerous applications [ 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%